Comportamiento materno durante la hospitalización del recién nacido - Jessica Janeth, Chisag Guevara. (2019)
The establishment of the mother-child link continuously generates the maturity and development of the newborn, but also modifies the maternal behavior causing several changes in the binomial. The purpose of this research is to describe the most important generalities related to the mother's behavior during hospitalization of the newborn in the intensive care unit. A bibliographic review is carried out, through the search of national and international scientific articles of indexed pages such as Scielo, ELSEVIER, Mediagraphic, ScienceDirect. It was concluded that during the hospitalization in the mothers, some stressful factors influence the development of the mother-child link, related to the unknown environment and feelings of anger, guilt, sadness and helplessness, which transcend into important behavioral changes divided into 6 categories such as: loss of self-control, pain experimentation, search for meaning to events, adaptation to the event, acquisition of the maternal role and unconditional love; being these part of the modification in the behavior of the mother when she is facing a stressful episode. It is important then, to identify the maternal response to the challenges they experience, looking for strategies aimed to reducing anxiety and stress, through emotional support during the acceptance stage and adaptation to their new maternal role.